SHIGELLOSIS - Maliy, V.P.; Volobueva, O.V.; Lyadova, T.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
In a lecture are presented etiologic, epidemiology, patogenetic and clinical description of shigellosis. Basic approaches to diagnostics, medical treatment and prophylaxis of disease are represented.